2022
DOI: 10.3390/infrastructures7090117
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Recycled Concrete Aggregate Using High Calcium Fly Ash Geopolymer as Pavement Base Material

Abstract: This research investigated high calcium fly ash geopolymer stabilized recycled concrete aggregate (RCA-FAG) as pavement base material. The effect of recycled concrete aggregate (RCA):high calcium fly ash (FA) ratios, sodium silicate (Na2SiO3):sodium hydroxide (NaOH) ratio, and curing time on the unconfined compressive strength (UCS) and scanning electron microscope (SEM) properties of RCA-FAG samples were evaluated. The maximum dry unit weight of the RCA-FAG sample was 20.73 kN/m3 at RCA:FA ratio of 80:20 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…For the production of geopolymer concrete, a fairly large range of different types of aluminosilicate components are used, which are mainly technogenic waste [8][9][10]. For example, in works [11][12][13][14], the authors developed various compositions of geopolymer concretes, where fly ash was used as an aluminosilicate component, and the strengths of the composites varied from 15 MPa to 70 MPa. In studies [15][16][17], various types of slag were used as a binder, and the strength of geopolymer composites varied from 40 MPa to 70 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…For the production of geopolymer concrete, a fairly large range of different types of aluminosilicate components are used, which are mainly technogenic waste [8][9][10]. For example, in works [11][12][13][14], the authors developed various compositions of geopolymer concretes, where fly ash was used as an aluminosilicate component, and the strengths of the composites varied from 15 MPa to 70 MPa. In studies [15][16][17], various types of slag were used as a binder, and the strength of geopolymer composites varied from 40 MPa to 70 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…Micheli et al [ 21 ] found that blending carbon nanotubes in concrete could enhance its electromagnetic shielding effectiveness. Tiyasangthong et al [ 22 ] evaluated the possibility of using high-calcium fly ash geopolymers to stabilize a recycled concrete aggregate. Huang et al [ 23 ] studied the deicing efficiency of concrete surfaces with added carbon fibers under multiple factors and obtained an optimum fiber length of 0.6 cm, while the initial temperature and the ice layer had little effect on microwave heating.…”
Section: Introductionmentioning
confidence: 99%
“…The unconfined compressive strength of the fly ash geopolymer base material improved by 23 percent, from 13.1 MPa to 17.1 MPa. Sermsak et al [ 27 ] reported that the 7 day unconfined compressive strength of recycled concrete aggregate, fly ash geopolymer improved as the fly ash (FA) content increased. This is because FA silica and alumina can react with calcium, resulting in pozzolan and geopolymerization products, which met the requirements for a low-traffic road.…”
Section: Introductionmentioning
confidence: 99%